Auditoría: aspectos legales en una pandemia - Vitalii Olyukha; Vladimira Dobrovolska; Valentyna Chaikovska; Vadim Popeliuk; Juliіa Dyshkantiuk (Ius Humani. Jornal do direito, 2020)
This article is devoted to changes in the economic and legal conditions of audit activity in the context of a pandemic and its consequences. It will be useful both to top managers of companies and to audit companies and their specialists. The object of the research is public relations in the field of auditing. The interests of the three main parties are distinguished separately: states, business and auditing companies. The work has the following structure: world experience in auditing during a pandemic; national legal framework for auditing: problems and solutions; the current state of the audit services market: problems and solutions; recommendations to the participants of the audit market. The research methodology is based on general and special scientific methods, in particular: historical-legal, formal-legal, comparative analysis, and modeling. The study concludes that it is the audit system that still acts as a locomotive for the business environment, since an audit is at the forefront of the latest technological solutions (processing Big Data, leveling information asymmetry), is able to quickly work with financial and economic reporting data and propose appropriate measures. However, for this, the business should not be afraid to change in the wake of this new changing world, and audit companies should quickly adapt to new trends and needs.